Public housing and unemployment: Skills and spatial mismatch in postindustrial Hong Kong - Paavo Monkkonen (University of California, Institute of Urban and Regional Development (IURD), 2011)
The impact of living in public rental housing on employment has been the subject of debate internationally. Theory suggests that restrictions on residential mobility, neighborhood effects, and the place-based housing subsidy itself contribute to the higher rates of unemployment often observed among public housing tenants. However, recent evidence from Europe and Australia show that when proper consideration is given to the endogeneity of housing tenure and employment, the effect of living in public housing on employment loses significance. This paper examines the employment outcomes of Hong Kong's public housing tenants. Hypothesis tests using simultaneous probit models find that it continues to have a statistically significant and large positive impact on the probability of being unemployed. Yet, a high rate of unemployment among public housing residents in Hong Kong is a relatively recent phenomenon, thus the paper also examines changes in the characteristics of public housing residents and the spatial connection between housing and employment in the city, using one percent sample datasets of Hong Kong population censuses from 1986 to 2006. The location of public rental housing is found to have a strong influence on the employment outcomes of residents.
Keywords: R23; R38; J61; J64; 330; public housing; unemployment; spatial mismatch; Sozialer Wohnungsbau; Arbeitslosigkeit; Wohnungswechsel; Regionale Disparität; Hongkong